Status of professional instrumentation practice and surgical area graduates in Paraguay. - Morales-Clemotte, Lelis Noelia; Agüero Chamorro, Débora Claudia (Medicina Clínica y Social, 2024)
Objective: to know the work environment of the professional and licensed Surgical Instrument Technician in Paraguay. Methodology: descriptive, quantitative and cross-sectional study. The sample is 167 graduates, graduates of public and private institutions. Non-probability sampling for convenience, the data collection instrument is an electronic questionnaire. Results: 74% are women, 50% have an age range between 21 and 30 years old, 79.6% graduated from a public institution, 40% say they have moderate difficulty finding their first job in the field. Access to employment, 71% was through personal contacts, 72% is dedicated to work as Instrument Technicians, 60% have a job seniority of 1 to 5 years. Among the postgraduates, 30% are university didactics certified. Discussion: Surgical Instrument Technicians meet the requirements to perform other functions in addition to instrumentation and circulating nurses in the operating room. Similarly, other studies show less participation in the administrative area, teaching, marketing and sales. 20 years have elapsed since the first Technicians graduated, being a new profession, not given the importance it deserves. It is noteworthy that the state can save economic resources by hiring Surgical Instrument Technicians, since they are experts in aseptic care and competent in minimizing the amount of time the patient spends in surgery.
Keywords: surgical instrumentation; , professional profile; labor field; instrumentation in Paraguay